2011
DOI: 10.1152/ajpregu.00342.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of macronutrients, age, and obesity on 6- and 24-h postprandial glucose metabolism in cats

Abstract: . Effect of macronutrients, age, and obesity on 6-and 24-h postprandial glucose metabolism in cats. Am J Physiol Regul Integr Comp Physiol 301: R1798 -R1807, 2011. First published September 21, 2011 doi:10.1152/ajpregu.00342.2011.-Obesity and age are risk factors for feline diabetes. This study aimed to test the hypothesis that age, long-term obesity, and dietary composition would lead to peripheral and hepatorenal insulin resistance, indicated by higher endogenous glucose production (EGP) in the fasted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
4
2

Year Published

2012
2012
2025
2025

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 73 publications
6
34
4
2
Order By: Relevance
“…Pyruvate cycling, PEPCK, and CS flux were all closely correlated both early and late in the fast, much more so than has been observed in other species (6,30,42). Such close correlation suggests coordinated regulation of these pathways during the postweaning fast (Table 5).…”
Section: Discussionmentioning
confidence: 53%
“…Pyruvate cycling, PEPCK, and CS flux were all closely correlated both early and late in the fast, much more so than has been observed in other species (6,30,42). Such close correlation suggests coordinated regulation of these pathways during the postweaning fast (Table 5).…”
Section: Discussionmentioning
confidence: 53%
“…26 Additionally, both basal insulin concentrations and insulin area under the curve during IVGTT are increased in obese dogs and cats, as they are in other mammals. [26][27][28][29][30] In the aforementioned longitudinal studies of feline obesity, these changes were apparent with as little as 10% gain over lean body weight (Fig. 1).…”
Section: Box 1 Adipose Tissue Dysfunction In Obesitymentioning
confidence: 94%
“…19,20 There are few data, however, to support these concerns. Although some studies have shown a greater postprandial blood glucose concentration or alterations in glucose tolerance in cats after ingesting of high-carbohydrate, low-protein diets, [21][22][23] other studies have found no such effects, 17,[24][25][26][27] indicating that components other than the amount of carbohydrate in the diet influence this effect. The feeding method (eg, single meal daily vs multiple meals or continuous access to food) also alters the glucose response with higher glucose peaks after a single large meal.…”
Section: Body Weight and Body Composition Changes With Agementioning
confidence: 99%